Integrierte Projektabwicklung mit Mehrparteienverträgen Untersuchungen zur Wirkung der vertraglichen Gestaltungsoptionen - Budau, Maximilian Rolf-Dieter (Karlsruher Reihe Technologie und Management im Baubetrieb, 2024)
In the context of IPA projects, project participants generally try to create a system that aligns the individual interests of the participants in such a way that opportunistic behavior of the participants does not have negative consequences for the project as a whole. This paper systematizes the current state of knowledge on IPA and examines the economics of these approaches.